Compositional regulation of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) by replacement of granule-associated protein in Ralstonia eutropha. Issue 1 (December 2015) - Kawashima, Yui; Orita, Izumi; Nakamura, Satoshi; Fukui, Toshiaki
Abstract Background Phasin (PhaP), a kind of polyhydroxyalkanoate (PHA) granule-associated proteins, has a role in controlling the properties of PHA granules surface, and is thought to have influence on PHA biosynthesis in PHA-producing bacteria. This study focused on thephaP1 Re locus inRalstonia eutropha as a site of chromosomal modification for production of flexible poly(3-hydroxybutyrate-co -3-hydroxyhexanoate) [P(3HB-co -3HHx)] from soybean oil. Results Considering the high expression level ofphaP1 Re, phaJ Ac [encoding (R )-specific enoyl-CoA hydratase fromAeromonas caviae ] was inserted into the downstream ofphaP1 Re on chromosome 1 ofR. eutropha strain NSDG harboringphaC NSDG (encoding PHA synthase with broad substrate specificity). The constructed strain efficiently accumulated P(3HB-co -3HHx) on soybean oil with higher 3HHx composition when compared to the previous strain havingphaJ Ac withinpha operon. Insertion of the secondphaC NSDG along withphaJ Ac at thephaP1 Re locus led to incorporation of much larger 3HHx fraction into PHA chains, although the molecular weight was markedly reduced. TheR. eutropha strains were further engineered by replacingphaP1 Re withphaP Ac (encoding phasin fromA. caviae ) on the chromosome. Interestingly, the phasin replacement increased 3HHx composition in the soybean oil-based PHA with keeping high cellular contents, nevertheless no modification was conducted in the metabolic pathways. Kinetic and Western blot analyses of PHA synthase using cellular insoluble fractions strongly suggested that the phasin replacement not only enhanced activity of PHA synthase fromA. caviae but also increased affinity especially to longer (R )-3HHx-CoA. It was supposed that the increased affinity of PHA synthase to (R )-3HHx-CoA was responsible for the higher 3HHx composition in the copolyester. Conclusions The downstream ofphaP1 Re was a useful site for integration of genes to be overexpressed during PHA accumulation inR. eutropha . The results also clarified that polymerization properties of PHA synthase was affected by the kind of phasin co-existed on the surface of PHA granules, leading to altered composition of the resulting P(3HB-co -3HHx). The phasin replacement is a novel engineering strategy for regulation of composition of PHA copolyesters.